THE RELATIONSHIP OF MOTHER'S KNOWLEDGE ABOUT THE MOVEMENTS OF THE FIRST 1000 DAYS OF LIFE (HPK) AND THE INCIDENT OF STUNTING IN TODDLER IN THE WORKING AREA OF THE SINGKOHOR PUSKESMAS UPTD, 2024 - Fitriani Bancin; Ricca Nophia Amra; Rizka Sititah Rambe, (Mitra Husada Health Internasional Conference (MIHHICo), 2024)
Stunting or often called stunting is a condition of impaired growth (body and brain growth) in children under 5 years old (toddlers) due to chronic malnutrition and recurrent infections, especially during the First 1000 Days of Life (HPK). The aim of this research is to find out Relationship between mother's knowledge regarding the first 1000 days of life (HPK) movement in the UPTD work area of Singkohor Community Health Center in 2024. The design of this research is analytical with a cross-sectional approach using primary and secondary data. The sampling technique in this research used simple random sampling, totaling 95 respondents. The measuring instrument used is a questionnaire. Data collection using observation sheets then analysis using a computerized system. The results of statistical tests using the chi-square test with a confidence level of 95% df 1, obtained a p-value of 0.000<0.05, meaning Ho was rejected, so it was concluded that there was a relationship between maternal knowledge about the First 1000 Days of Life (HPK) movement and the incidence of stunting in toddlers in the UPTD Working Area of Singkohor Community Health Center, Singkohor District, Aceh Singkil City in 2024. It is hoped that from the results of this research mothers can increase information, counseling and knowledge about preventing stunting in toddlers by means of nutritional interventions aimed at the first 1000 days of life (HPK).